Covid-19 pandemic effects on popular physical education and sports in Russia - Stolyarov, V. I.; Abalyan, A. G.; Fomichenko, T. G.; Vorobyov, S. A (Theory and Practice of Physical Culture, 2021)
Objective of the study was to survey the COVID-19 pandemic effects on the popular physical education and sports in Russia by the population groups and health categories.